2022
DOI: 10.3389/fnagi.2022.821789
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genetic Networks Reveals Complex Associations and Risk Trajectory Linking Mild Cognitive Impairment to Alzheimer’s Disease

Abstract: Amnestic mild cognitive impairment (aMCI) and sporadic Alzheimer’s disease (AD) are multifactorial conditions resulting from a complex crosstalk among multiple molecular and biological processes. The present study investigates the association of variants localized in genes and miRNAs with aMCI and AD, which may represent susceptibility, prognostic biomarkers or multi-target treatment options for such conditions. We included 371 patients (217 aMCI and 154 AD) and 503 healthy controls, which were genotyped for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…and plays an important role in balancing Ang II by converting excess Ang II to Ang -(1-7) in the central nervous system. Ang -(1-7) acts on its receptor Mas, in recent studies, ACE 2/Ang-(1-7)/Mas axis has been shown to play a neuroprotective role in a variety of neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease [17,18] , and may be associated with mild cognitive impairment and susceptibility to Alzheimer's disease [19] . However, it remains uncertain whether the ACE2/Ang -(1-7)/Mas axis participates in t he development of cognitive impairment induced by long-term isoflurane anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…and plays an important role in balancing Ang II by converting excess Ang II to Ang -(1-7) in the central nervous system. Ang -(1-7) acts on its receptor Mas, in recent studies, ACE 2/Ang-(1-7)/Mas axis has been shown to play a neuroprotective role in a variety of neurodegenerative diseases such as Alzheimer's disease and Parkinson's disease [17,18] , and may be associated with mild cognitive impairment and susceptibility to Alzheimer's disease [19] . However, it remains uncertain whether the ACE2/Ang -(1-7)/Mas axis participates in t he development of cognitive impairment induced by long-term isoflurane anesthesia.…”
Section: Introductionmentioning
confidence: 99%